Physiotherapy for people with painful peripheral neuropathies: a narrative review of its efficacy and safety - Jesson, T; Runge, N; Schmid, AB (Wolters Kluwer Health, 2020)
Pharmacological treatment for peripheral neuropathic pain has only modest effects and is often limited by serious adverse responses. Alternative treatment approaches including physiotherapy management have thus gained interest in the management of people with peripheral neuropathies. This narrative review summarises the current literature on the efficacy and safety of physiotherapy to reduce pain and disability in people with radicular pain and chemotherapy-induced peripheral neuropathy, 2 common peripheral neuropathies. For chemotherapy-induced peripheral neuropathy, the current evidence based on 8 randomised controlled trials suggests that exercise may reduce symptoms in patients with established neuropathy, but there is a lack of evidence for its preventative effect in patients who do not yet have symptoms. For radicular pain, most of the 21 trials investigated interventions targeted at improving motor control or reducing neural mechanosensitivity. The results were equivocal, with some indication that neural tissue management may show some benefits in reducing pain. Adverse events to physiotherapy seemed rare; however, these were not consistently reported across all studies. Although it is encouraging to see that the evidence base for physiotherapy in the treatment of peripheral neuropathic pain is growing steadily, the mixed quality of available studies currently prevents firm treatment recommendations. Based on promising preliminary data, suggestions are made on potential directions to move the field forward.